The boys are back [videorecording] - Cubitt, Allan; Hicks, Scott; Owen, Clive; Booth, Emma, 1982-; Fraser, Laura, 1976-; MacKay, George, 1992-; Carr, Simon, 1952- (Miramax Films ; Distributed by Buena Vista Home Entertainment, 2010)
After the unexpected death of his wife, a sportswriter finds himself consumed with grief and completely unprepared to raise two boys. Determined to bring joy back into their lives, he takes a 'just say yes' approach to parenting. And as freedom reigns, chaos ensues.